2016
DOI: 10.1051/0004-6361/201628556
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the periodicities in radio and GeV emission from LS I +61°303

Abstract: Context. One possible scenario to explain the emission from the stellar binary system LS I +61• 303 is that the observed flux is emitted by precessing jets powered by accretion. Accretion models predict two ejections along the eccentric orbit of LS I +61• 303: one major ejection at periastron and a second, lower ejection towards apastron. Our GeV gamma-ray observations show two peaks along the orbit (orbital period P 1 ) but reveal that at apastron the emission is also affected by a second periodicity, P 2 . S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 53 publications
13
29
0
Order By: Relevance
“…4 in Massi & Torricelli-Ciamponi 2016 and references therein), Be star variations last 2-3 cycles only and are of different lengths (Rivinius et al 2013). Timing analysis of 37 years of radio data performed by reveals that LS I +61 • 303 does not show merely 2-3 cycles which are of different lengths but a repetition of 8 full cycles of an identical length of 1628 days, well in agreement with the scenario of a microquasar with a precessing jet (Massi & Torricelli-Ciamponi 2014;Jaron et al 2016). In addition, as discussed in Jaron et al (2016), the orbital shift in the equivalent width of the Hα emission line (Paredes-Fortuny et al 2015), points to variations caused by a precessing jet.…”
Section: The Binary System Ls I +61 • 303supporting
confidence: 68%
“…4 in Massi & Torricelli-Ciamponi 2016 and references therein), Be star variations last 2-3 cycles only and are of different lengths (Rivinius et al 2013). Timing analysis of 37 years of radio data performed by reveals that LS I +61 • 303 does not show merely 2-3 cycles which are of different lengths but a repetition of 8 full cycles of an identical length of 1628 days, well in agreement with the scenario of a microquasar with a precessing jet (Massi & Torricelli-Ciamponi 2014;Jaron et al 2016). In addition, as discussed in Jaron et al (2016), the orbital shift in the equivalent width of the Hα emission line (Paredes-Fortuny et al 2015), points to variations caused by a precessing jet.…”
Section: The Binary System Ls I +61 • 303supporting
confidence: 68%
“…Furthermore, through frequency radio studies it has been suggested that there are actually two close periods of ≈ 26.5 and ≈ 26.9 d modulating the emission of LS I +61 303, and the superorbital modulation is just the beating period between them [57,58,59]. In this case, we would assume the presence of a precessing jet with a period close to the orbital period of the system, naturally explaining the regularity of the long-term emission [60,61].…”
Section: Microquasar Scenariomentioning
confidence: 87%
“…Accretion-based models and pulsar-wind interaction scenarios keep being discussed as the powering engine of GBs (see e.g. Dubus 2006;Bosch-Ramon et al 2006b;Romero et al 2007;Torres et al 2012;Jaron et al 2016). An up-to-date summary accounting for some of the key properties of currently known GBs (not including 4FGL J1405.1-6119) is provided in (Paredes & Bordas 2019a) and Paredes & Bordas 2019b.…”
Section: Relativistic Outflows From Gamma-ray Binariesmentioning
confidence: 99%